Effluent conditioning of biodiesel production for biological treatment using clay as a separation coadjutant - Correia, Lívia Caroline; Silva, Romário Ribeiro; França, Fernanda Rocha Morais; da Silva, Gabriel Francisco; Coêlho, Diego F.; Marques, José Jailton (Scientia Plena, 2020)
Biodiesel is a renewable, non-toxic and sustainable biofuel, considered to be the main candidate for a fossil fuel alternative in many countries. However, its manufacturing process results in about 0.2 to 3 L of effluent per litre of biodiesel produced. In addition to an inherently high organic load, its composition includes by-products, traces of unreacted chemicals and catalysts, which inhibit microorganism growth and prevent its direct treatment by tertiary methods. In this context, this work aims to evaluate the combination of the coagulation-flocculation technique with dissolved air flotation (DAF). Real wastewater samples were obtained by synthesising biodiesel from soybean oil in-loco and performing the required washing procedures. The highest turbidity reduction efficiency (92.03%) was obtained using 1200 of clay. By using response surface methodology, it was possible to analyse the effect of the chosen experimental factors and show that the best results (81.28%, 58.95% and 89.34% for turbidity, oil and grease and chemical oxygen demand - respectively) were obtained using 925 of clay and 1000 of coagulant. Ultimately, clay proved to be an efficient coadjutant in the removal of organic matter, oils, grease, suspended solids and soluble organic matter from the biodiesel wastewater. Moreover, its low cost over traditional flocculants makes it an attractive alternative to industrial wastewater treatment processes.